A lncRNA Perspective into (Re)Building the Heart - Frank, Stefan; Aguirre, Aitor; Hescheler, Juergen; Kurian, Leo (Frontiers in Cell and Developmental Biology, 2016)
Our conception of the human genome, long focused on the 2% that codes for proteins, has profoundly changed since its first draft assembly in 2001. Since then, an unanticipatedly expansive functionality and convolution has been attributed to the majority of the genome that is transcribed in a cell-type/context-specific manner into transcripts with no apparent protein coding ability. While the majority of these transcripts, currently annotated as long non-coding RNAs (lncRNAs), are functionally uncharacterized, their prominent role in embryonic development and tissue homeostasis, especially in the context of the heart, is emerging. In this review, we summarize and discuss the latest advances in understanding the relevance of lncRNAs in (re)building the heart.